The Role and Authority of the Deputy Regional Head According to Islamic Principles within the Framework of Regional Government Law - Hariyanto, Hariyanto; Mukhlis, Muhammad Mutawalli; Rismana, Daud (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The position of the deputy regional head in Indonesia's regional government system is often unclear, particularly within constitutional and legal context. This ambiguity leads to inefficiencies and conflicts in governance. This study seeks to examine the role of the deputy regional head from the perspective of fiqh siyasah, addressing the legal uncertainties and suggesting ways to enhance their authority. Utilizing a normative juridical approach, this research draws on secondary data from legal documents, academic articles, and other pertinent sources. Data were gathered through a structured literature review, and qualitative analysis was conducted using juridical methods to create a descriptive narrative. The findings indicate that the authority of the deputy regional head is frequently overshadowed by the regional head, relegating their role to mostly ceremonial or minor administrative tasks. This disparity contradicts Islamic governance principles, which prioritize justice, consultation, and accountability. This study contributes to the field by proposing a Principle-Based Authorization Model aimed at redefining the deputy’s authority in a way that aligns with both Islamic values and contemporary governance requirements. This model is recommended as a foundation for legal and policy reforms to promote more effective and cohesive regional governance.